PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, IKLIM ORGANISASI, KEPUASAN KERJA DAN KOMITMEN AFEKTIF TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PEGAWAI PT. PDAM TIRTA WIJAYA CILACAP - Alfato Yusnar Kharismasyah; Surya Kusuma Putra (Jurnal Manajemen, 2020)
ABSTRACT The purpose of this research aims to analyze and explain the effect of transformational leadership, organizational climate, job satisfaction and affective commitment on organizational citizenship behavior (OCB) employees of PDAM Tirta Wijaya Cilacap Regency. This study uses a quantitative approach. The sampling technique uses purposive sampling method and Slovin formula. This study uses a questionnaire with the number of respondents 131 permanent employees of PDAM Tirta Wijaya Cilacap Regency. Data analysis uses validity test, classic assumption test, multiple linear regression test, coefficient of determination test, t test and f test. From the results of the study show that transformational leadership, organizational climate, job satisfaction and affective commitment have a significant effect both partially and simultaneously so the company must increase the variables that can affect OCB in order to create company goals. This research also suggests further research to add other variables not examined in order to strengthen the relationship of each variable with OCB. Keywords: Transformational leadership, organizational climate, job satisfaction, affective commitment and organizational citizenship behavior (OCB).